The Influence of Work Facilities and Work Discipline on Employee Performance at the Regional Library Service (DPAD) of Bima City - Ruri Hardyanti; Mulyadin; Badar (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
He purpose of this research is to find out whether there is a significant influence between work facilities and work discipline on employee performance at the Bima City Regional Library Service (DPAD). This type of research includes associative research, which is a method used to determine the relationship between two or more variables, population. In this study there were 50 employees, with ASN details of 36 employees and 14 contract employees. So with this the researcher determined a sample of 36 ASN which could represent the large population of 50 respondents. The type of data used in this research is Data Qualitative Data, Data collection techniques used are (a) literature study (b) documentation (c) questionnaire, Research location at Bima City Regional Library Service (DPAD). on Jl. Breadfruit, No. 03 , karara, Mpunda, Kota. Bima, Nusa Tenggara Bar. 84115, and the data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, t test and F test.The results of the research show that there is a significant influence between work facilities on employee performance at the Regional Library Service (DPAD) of Bima City, there is a significant influence between work discipline on employee performance at the Bima City Regional Library Service (DPAD) and there is a simultaneous relationship between Facilities and Work Discipline On Employee Performance at the Bima City Regional Library Service (DPAD).